Clustering patterns of physical activity, sedentary and dietary behavior among European adolescents: The HELENA study - Manios Yannis; Rey-López Juan P; Kersting Mathilde; Gottrand Frederic; Zaccaria Maria; Dallongeville Jean; Cuenca-Garcia Magdalena; De Bourdeaudhuij Ilse; Benser Jasmin; Huybrechts Inge; Ottevaere Charlene; Molnár Dénes; et al. (BMC, 2011)
Abstract Background Evidence suggests possible synergetic effects of multiple lifestyle behaviors on health risks like obesity and other health outcomes. A better insight in the clustering of those behaviors, could help to identify groups who are at risk in developing chronic diseases. This study examines the prevalence and clustering of physical activity, sedentary and dietary patterns among European adolescents and investigates if the identified clusters could be characterized by socio-demographic factors. Methods The study comprised a total of 2084 adolescents (45.6% male), from eight European cities participating in the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) study. Physical activity and sedentary behavior were measured using self-reported questionnaires and diet quality was assessed based on dietary recall. Based on the results of those three indices, cluster analyses were performed. To identify gender differences and associations with socio-demographic variables, chi-square tests were executed. Results Five stable and meaningful clusters were found. Only 18% of the adolescents showed healthy and 21% unhealthy scores on all three included indices. Males were highly presented in the cluster with high levels of moderate to vigorous physical activity (MVPA) and low quality diets. The clusters with low levels of MVPA and high quality diets comprised more female adolescents. Adolescents with low educated parents had diets of lower quality and spent more time in sedentary activities. In addition, the clusters with high levels of MVPA comprised more adolescents of the younger age category. Conclusion In order to develop effective primary prevention strategies, it would be important to consider multiple health indices when identifying high risk groups.